(3eYQaI GdCdbGHs - (3CHh GdaVd eMeO Hf WGgQ Hf Ydj GdebOSi hjYQa HGHf GdbjSQGfi GdTjHGfis; (3CMeO Hf YHO GdQMef Hf CMeO Hf ehSi GdTjQGRj, CHh HcQ GdaGQSj GdTjQGRj,J (B407 (3g` s ((3GHf GdGfeGWi s)
(3ChdgG (B:s
(3GdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B201 - (3U(B217s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B146s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B265 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs